Effects of ethanol, methyl tert-butyl ether and gasoline-hydrogen blend on performance parameters and HC emission at Wankel engine. Issue 3 (2nd April 2020) - Yontar, Ahmet Alper
Abstract: This study focuses on determining the effects of gasoline, ethanol, methyl tert-butyl ether (MTBE) and a gasoline–hydrogen mixture (G98H2) on engine performance and hydrocarbon (HC) emission for a Wankel engine. Engine speed range tests were performed by varying the engine speed from 1000 to 6000 rpm by increments of 500 rpm at full load. Lambda effects tests were carried out between 0.8 and 1.2 at maximum engine torque speed and maximum engine power speed. The engine speed test results show that the maximum power is approximately 7.91% higher than that of gasoline at G98H2. The power for MTBE is approximately 5.25% lower than that of ethanol. The HC formation range was 81–101, 80–97, 77–93 and 73–92 ppm for gasoline, MTBE, ethanol and G98H2, respectively. At maximum torque speed, the lambda effect tests show that the power is approximately 5.91% higher than that of gasoline for G98H2. The HC formation for G98H2 is overall 7.05% and 6.15% lower than for gasoline and MTBE, respectively. For maximum power speed lambda tests, the power is approximately 7.52% higher than that of gasoline. The power for ethanol is approximately 12.19% lower than for gasoline at G98H2. The HC formation for gasoline is overall 5.81% and 4.65% higher than for ethanol and G98H2, respectively.